2016
DOI: 10.1016/j.ajme.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of occult hepatitis B virus among chronic hepatitis C patients

Abstract: Background: Concurrent infections with hepatitis B virus (HBV) and hepatitis C virus (HCV) are increasingly recognized in patients with chronic hepatitis. In Egypt, the last decade showed a remarkable decline in HBV infection associated with remarkable rise in HCV infection. The probable impact of occult HBV in patients with chronic HCV infection has been previously investigated and the evidence suggests a possible correlation with lower response to anti-viral treatment, higher grades of liver histological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…OBI is frequently found in patients with chronic hepatitis C (CHC)[ 85 ]. A range of prevalence rates from 3.2% to 90.9%[ 21 , 86 ] and all studies found were conducted in Egypt[ 87 - 91 ] (Table 2 ). A low prevalence of 3.2% was found in blood donors[ 86 ], whereas the highest prevalence of 90.9% was found in patients undergoing antiviral therapy for hepatitis C[ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…OBI is frequently found in patients with chronic hepatitis C (CHC)[ 85 ]. A range of prevalence rates from 3.2% to 90.9%[ 21 , 86 ] and all studies found were conducted in Egypt[ 87 - 91 ] (Table 2 ). A low prevalence of 3.2% was found in blood donors[ 86 ], whereas the highest prevalence of 90.9% was found in patients undergoing antiviral therapy for hepatitis C[ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, there was a significant association between CHC and OBI (Table 1). It is widely agreed that patients with CHC represent a category of individuals with a high prevalence of OBI (El Sheredy et al, 2015;Mahmoud et al, 2016). History of blood transfusion had no impact on OBI (Table 2), a finding that could be credited to the rigorous procedures routinely used in Egypt to make blood transfusion safe.…”
Section: Discussionmentioning
confidence: 98%
“…This has serious implications in that out of every 10 people who test negative for HBsAg in the country, 2 have OBI and are at serious risk of transmission. Experts have recently recommended the use of highly sensitive nested PCR or real-time PCR assays that can detect fewer than 10 copies of HBV DNA for the screening and identification of OBI ( 101 ), especially in high-risk groups such as HIV, liver disease and hemodialysis patients. Such early detection and timely treatment reduces the risk of hospital cross-infection, and prevents health care infection and unnecessary medical disputes.…”
Section: Discussionmentioning
confidence: 99%